2013
DOI: 10.1161/circulationaha.113.002428
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Technologies Are Associated With Cardiovascular Remodeling In Utero That Persists Postnatally

Abstract: A ssisted reproductive technologies (ARTs), mainly standard in vitro fertilization or intracytoplasmic sperm injection, permit childbirth in many infertile couples and nowadays represent 1% to 4% of births in developed countries.1 Although these technologies are generally considered safe, the potential association of ART with poorer pregnancy outcomes has long been investigated. There is evidence that ART is associated with increased risk for adverse perinatal outcome and congenital malformations.2 This notwit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
157
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(184 citation statements)
references
References 38 publications
19
157
3
5
Order By: Relevance
“…Gratacos et al showed that ART is associated with in utero cardiac remodelling that persists in 6 month old infants [55]. We subsequently demonstrated that cardiac alterations persist into adolescence, as evidenced by larger right ventricular end-diastolic volume and diastolic dysfunction at high altitude [56].…”
Section: Early Embryonic Insults: Assisted Reproductive Technology (Asupporting
confidence: 53%
“…Gratacos et al showed that ART is associated with in utero cardiac remodelling that persists in 6 month old infants [55]. We subsequently demonstrated that cardiac alterations persist into adolescence, as evidenced by larger right ventricular end-diastolic volume and diastolic dysfunction at high altitude [56].…”
Section: Early Embryonic Insults: Assisted Reproductive Technology (Asupporting
confidence: 53%
“…Since it was initially proposed that conception via ART might be linked to an increased risk of developing long-term cardiovascular health issues, several studies have confirmed an altered cardiovascular phenotype and elevated metabolic risk in children born following IVF [13,14]. For example, investigations have shown that IVF-conceived children have significantly higher blood pressure compared with spontaneously conceived children [41][42][43][44], something that has recently been supported by a meta-analysis of 2112 children conceived by ART, where data showed that there was a slight, yet statistically significant, increase in blood pressure compared with naturally conceived offspring [45].…”
Section: Discussionmentioning
confidence: 99%
“…Multicenter epidemiological studies have shown that the incidence of cardiovascular malformations in ART babies is markedly increased compared with that of naturally conceived offspring [9][10][11]. Furthermore, follow-up surveys of ART-conceived offspring have shown an increased risk of dysfunction [12] and remodeling in the cardiovascular system [13], including higher arterial blood pressure, altered vascular intima-media thickness, and compromised myocardial regulatory function [14]. Investigations using mouse models have further illustrated that ART-conceived offspring have abnormal vascular endothelial function and changes in lipid metabolism [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…STUDIES IN ANIMALS AND HUMANS demonstrate that adverse events during early life induce vascular dysfunction that may predispose to premature cardiovascular morbidity and mortality (1,2,10,19,24). Assisted reproductive technologies (ART) represent a recent important example of this problem, since ART induces vascular and cardiac dysfunction in children (26,33,34) and causes premature vascular aging and arterial hypertension that are associated with a shortened life span in mice (20). Consistent with observations in humans suggesting that decreased nitric oxide [nitrate/nitrite (NOx)] bioavailability contributes to vascular dysfunction in the offspring of ART (22), data in ART mice indicate that epigenetic alterations of the endothelial nitric oxide synthase (eNOS) gene that translate into decreased vascular eNOS expression and NOx synthesis underpin premature vascular aging and arterial hypertension (20).…”
mentioning
confidence: 99%